A cooperative game theoretic analysis of incentives for microgrids in regulated electricity markets. (1st May 2016) - Lo Prete, Chiara; Hobbs, Benjamin F.
Highlights: We consider the introduction of a microgrid in a regulated electricity network. Interactions among market participants are assessed using cooperative game theory. We quantify how the microgrid affects prices, costs and benefits for all parties. Misalignment of social and private objectives can lead to inefficient market outcomes. Utility customers may reap most of the benefits of microgrid introduction. Abstract: We model the economic incentives for market participants to cooperate in the development of a microgrid in a small electricity network served by a regulated utility. The microgrid can provide energy, ancillary services, heat and enhanced reliability to its customers. Using the framework of cooperative game theory, assuming exchangeable utility and full public information, we quantify how microgrid development affects prices, costs and benefits for parties in the network under alternative sets of assumptions. Our analysis yields three main results. First, market failures mean that the misalignment between the social objective (market efficiency) and objectives of private parties (profit maximization and consumer surplus maximization) can incent investment in inefficient scale and types of microgrid installations. We discuss how regulators can facilitate the realization of efficient market outcomes. Second, if the regulator does not correctly anticipate the timing of microgrid introduction and does not account for it in the rate-making process, social benefits associated with microgrid development could be lower and suboptimal investments may take place, relative to the case in which there is no regulatory lag. Third, utility customers could reap most of the benefits of microgrid introduction, if microgrids result in lower electric rates for all customers. However, when regulated prices are above the marginal cost of power provided by the utility, introducing microgrids can instead raise rates and the resulting economic losses to utility customers might exceed the economic gains to the microgrid owner and its consumers. Our study shows how the cooperative game framework can be useful to regulators and policy makers for identifying the beneficiaries of microgrid promotion policies, and for correcting the market failures in utility pricing that can distort incentives for microgrid investment.